Effect of ASA on the risk of cerebrovascular ischemic events in patients with PFO. Issue 9 (27th July 2022) - Xu, Liang; Zhou, Chang; Pan, Xuemei; Zhou, Jun; Sun, Heng; Xu, Tao
Abstract: Background: Whether atrial septal aneurysm (ASA) increases the risk of cerebrovascular ischemic events in patients with patent foramen ovale (PFO) remains controversial. Objective: We constructed a detailed meta‐analysis to assess the effect of ASA on risk of cerebrovascular ischemic events in patients with PFO. Methods: Randomized controlled trials (RCTs) and observational studies (cohort studies and case‐control studies) that compared PFO‐ASA against PFO alone were included. Pooled odds ratios (OR) estimates and 95% CI were calculated using the fixed‐effect and random‐effect models. Results: Four RCTs and twelve observational studies (five cohort studies and seven case‐control studies) contributed to the meta‐analysis. The pooled results of case‐control studies showed that ASA increased the risk of cerebrovascular ischemic events in patients with PFO (fixed‐effect model: OR = 3.69; 95% CI: 2.67–5.09; p < 0.01, random‐effect model: OR = 3.63; 95% CI: 2.51–5.24; p < 0.01). However, poole results from RCTs (fixed‐effect model: OR = 1.24; 95% CI: 0.78–1.95; p = 0.36, random‐effect model: OR = 1.27; 95% CI: 0.78–2.08; p = 0.34) and cohort studies (fixed‐effect model: OR = 1.35; 95% CI: 0.81–2.23; p = 0.25, random‐effect model: OR = 1.40; 95% CI: 0.84–2.33; p = 0.20) found no evidence. Overall analysis showed that ASA increased the risk of cerebrovascular ischemic events (fixed‐effect model: OR = 2.30; 95% CI: 1.84–2.87; p < 0.01, random‐effect model: OR = 2.11; 95% CI: 1.48–3.01; p < 0.01). The sensitivity analysis confirmed the stability of all results. Conclusions: Although case‐control studies support ASA to increase the risk of cerebrovascular ischemic events in patients with PFO, RCTs and cohort studies challenged the credibility. Further prospective studies are needed to confirm the effect of ASA on patients with PFO.